Implementation of Treffinger Model assisted by Color Card Media to Enhance Students’ Mathematical Creativity Skills - Mustafa, Sriyanti; Arifin, Arifin; Fitriani, Fitriani (Jurnal Pendidikan MIPA, 2022)
This study aimed to find out the increase in students' creativity by using the Treffinger model assisted by color card media. This research used Class Action Research. The subject of the research was the VIII.3 grade students of Junior high school 1 Parepare. The data was collected using observation and tests. The research instrument was student activity observation sheets and test sheets for cycles 1 and 2. The data collected were analyzed by descriptive statistics technique. The result of the study showed that the implementation of the Treffinger model assisted by color card media can increase the mathematical creativity of the VIII.3 grade students of junior high school 1 Parepare. It can be indicated by the increase in the activity percentage with an average of 24.74% by cycle 1 was in the “fair” category (55.21%) to cycle 2 was in the “good” category (79.95%), and the increase of the achievement test was 24.53%. Keywords: color card, creativity, mathematics, Treffinger learning model. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp804-815